Academic SelfAcademic Self-Handicapping and Self-Regulating Learning Strategies for Student Engagement in Performance of G-Handicapping and Self-Regulating Learning Strategies for Student Engagement in Performance of Grade 8 Students in Araling Panlipunan - Endiape, Honey Kates A.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2023)
This research aims to explore the Academic Self-Handicapping and Self-Regulating Learning Strategies employed by Grade 8 students at Godofredo M. Tan Integrated School of Arts and Trades, with a focus on understanding their impact on student engagement and academic achievement in the subject Araling Panlipunan. The study utilized a descriptive-correlational design and employed a researcher-modified questionnaire as the primary data collection method. Mean Standard Deviations were used to assess students’ perceptions of academic self-handicapping and self-regulating learning strategies, while Pearson Correlation was used to determine the relationship between Academic Self-Handicapping, Self-Regulated Learning Strategies, and students’ engagement and performance in Araling Panlipunan and Mediation Analysis to see if there is effect on the students’ performance mediated by their engagement. The result revealed a significant but weak positive correlation between students’ engagement and their performance in Araling Panlipunan. Furthermore, the students’ engagement was found to fully mediate the impact of their perceived level of academic self-handicapping and self-regulated learning strategies on their performance in the subject. As a result, the hypothesis has been rejected. This study sheds light on the factors influencing student engagement and academic achievement in Araling Panlipunan, providing valuable insights into the learning strategies adopted by Grade 8 students.